El bono demográfico y su incidencia en el crecimiento económico del Ecuador en el periodo 1995-2014. - Palmay Paredes, Polet Maritza (2017)
n this research, an analysis of the influence of the demographic dividend on the economic growth of Ecuador over a period of 20 years (1995-2014) is carried out, which seeks to provide important information that shows the behavior of each variable through of tables and graphs. These will allow to better understand the development of the same in the period of study. The research is structured as follows: In Chapter I, Referential Framework is detailed the problem that gave rise to this research, the formulation of the problem, the objectives (general and specific), the justification and the importance of this research. In Chapter II, Theoretical Framework describes the antecedents, theories and foundations on which the variables under study are supported, that is to say, the demographic dividend and all its components as well as the economic growth. In Chapter III, Methodological Framework explains the methodology used in the present research and the analysis of both variables is performed to finally expose the relationship between them by estimating a multiple linear regression model elaborated in the Eviews program. Chapter IV sets out the conclusions and recommendations reached after the conclusion of the research. In Chapter V, Bibliography details all the bibliographic material that was used for the purposes of this investigation.